Between bussiness and "friendship": an analysis of management practices and the moral dimensions of drug dealing in rural contexts - Gil Rodríguez, Héctor (Revista de Antropología Social, 2026)
In our country, drug trafficking is highly prevalent. Its analysis has predominantly focused on disadvantages urban neighborhoods; however, in recent years it has begun to expand into rural areas. This study is based on a qualitative analysis of interviews with sellers (N=16) who distribute cocaine and marijuana in two municipalities in the province of Ávila. The objective is to trace their trajectories and analyze the management of their commercial networks, exploring the moral logics that sustain them. The results contribute to advancing knowledge about how these networks operate in closed markets, showing that sales practices are shaped by various ethical commitments and are crucially influenced by community norms.
Keywords: Drug trafficking; rural areas; closed markets; social supply; moral economy